S59 The Role of Lymphocytes in Acute Lung Injury. (19th November 2012) - Muir, R; Cross, M; O'Kane, CM; Craig, TR; Shyamsundar, M; McAuley, DF; Ingram, RJ
Abstract : Introduction: Acute lung injury (ALI) is caused by the uncontrolled activation immune cells, resulting in dysregulated inflammation which irreversibly damages the lung architecture and function. Whilst the role of myeloid cells in the pathophysiology of ALI is well established, the function of lymphoid cells is less well understood. Hypothesis: Lymphocytes may play a role inthe regulation of inflammation in acute lung injury. Methods: We have utilised both human and murine in vivo models of lipopolysaccharide(LPS) induced ALI, as well as patient samples, to characterise lung infiltrating cells by flow cytometry. Lymphocyte associated cytokines were quantified by luminex or via ex vivo stimulation andintra-cellular cytokine staining. Results: Rapid infiltration of T cells(both a β and a β T cells), including regulatory T cells (Tregs), NKT and NKcells was observed. The cytokine Interleukin (IL)-17 is a potent recruiter of neutrophilsto sites of inflammatory sites. We observed a significant elevation in IL-17 levels in bronchoalveolar lavage fluid (BALF) in the humans postLPS inhalation; high levels of IL-17 were also seen in BALF from ALI patients. AnIL-17 KO mouse was utilised to confirm the key role for this cytokine in neutro philrecruitment to the lung during ALI. The transcription factor RORγt induces transcription of the genes encoding IL-17. Flow cytometric analysis revealed RORγt+ lung lymphocytes were predominantly CD4+ T cells (18%), CD8+ T cells (20%)and the recently described innate lymphoid cells (40%). Small percentages of RORγt+natural killer (NK) cells, NK T cells, gamma delta T cells were also seen. The role of Tregs in the early regulation of ALI was examined using a Treg inducibleKO murine model (FOXP3GFP DTR). When Tregs were depleted prior to LPS administration there was an increased recruitment of neutrophils into the lung. Conclusion: We have demonstrated that both lymphocyte released IL-17 and Tregs modulate the recruitment of neutrophils to the lung in ALI. These results reveal the importance of lymphocytes in the immunopathology of ALI. Increased understanding of the lymphocyte function could open new avenues of exploration for therapeutic strategies to regulate immune responses in ALI.